Plants have neither synapses nor a nervous system - Robinson, David G.; Draguhn, Andreas (Journal of plant physiology, 2021)
The alleged existence of so-called synapses or equivalent structures in plants provided the basis for the concept of Plant Neurobiology (Baluska et al., 2005; Brenner et al., 2006). More recently, supporters of this controversial theory have even speculated that the phloem acts as a kind of nerve system serving long distance electrical signaling (Mediano et al., 2021; Baluska and Mancuso, 2021). In this review we have critically examined the literature cited by these authors and arrive at a completely different conclusion. Plants do not have any structures resembling animal synapses (neither chemical nor electrical). While they certainly do have complex cell contacts and signaling mechanisms, none of these structures provides a basis for neuronal-like synaptic transmission. Likewise, the phloem is undoubtedly a conduit for the propagation of electrical signaling, but the characteristics of this process are in no way comparable to the events underlying information processing in neuronal networks. This has obvious implications in regard to far-going speculations into the realms of cognition, sentience and consciousness.